Is Isolated tricuspid regurgitation different from functional tricuspid regurgitation?. (25th November 2020) - Vieitez Florez, J.M; Monteagudo, J.M; Mahia, P; Marco, I; Gonzalez, T; Sitges, M; Bouzas, A; Gonzalez, V; Alonso, D; Carrasco, F; Adeba, A; Hinojar, R; et al.
Abstract: Introduction: Isolated tricuspid regurgitation (TR) prevalence is increasing in the last decades. Its presence is associated with a worse prognosis when EROA is >40 mm 2 . Because of high surgery risk and increasing incidence, isolated TR is a challenge in modern cardiology. Purpose: To evaluate the prevalence and characteristics of isolated TR compared to other TR aetiologies in a large cohort of patients. Methods: Prospective study where consecutive patients undergoing an echocardiographic study within a three-month period were included. All studies with at least moderate TR were selected. Isolated TR was defined as TR with no likely pulmonary hypertension (>50 mmHg), no overt TR cause (no intrinsic tricuspid disease, LVEF ≥50%, no pacemaker/defibrillator wire across the tricuspid, no other significant valve disease, no disease that may cause TR, no congenital or pericardial heart disease); and no previous valve surgery. Patients with isolated TR and other aetiologies were compared. Results: 2121 patients with at least moderate TR were included. Isolated TR was found in 398 patients (18.8%). Basal characteristics are shown in table 1. Patients with isolated TR did not have a higher prevalence of AF (47.5% vs. 48.6% p=0.362). Isolated TR was less severe (20.5% vs. 32.1% of patients with severe TR; p<0.001) and less symptomatic (NYHA ≥ II in 27.8% of patients vs. 69.3%; p<0.001). After selecting patients with at least severe TR, patients with isolated TR were also less symptomatic (NYHA≥II in 47.8% of patients vs. 70.7%; p<0.001) and they had better RV function (TAPSE <17 mm in 13.4% vs. 35.6%; p=0.001). We found that patients with isolated severe TR had a larger tricuspid annulus diameter (25.4±0.8 mm/m 2 vs. 24.0±0.3 mm/m 2 ; p=0.047). Conclusions: In this large prospective study, isolated TR is present in 18.8% of significant TR. Isolated TR was less severe, was associated with less RV dilatation (but with larger tricuspid annulus diameter) and patients had a better functional class compared to other TR aetiologies. Funding Acknowledgement: Type of funding source: None